Chronic post‐stroke oropharyngeal dysphagia is associated with impaired cortical activation to pharyngeal sensory inputs. (5th September 2017) - Cabib, C.; Ortega, O.; Vilardell, N.; Mundet, L.; Clavé, P.; Rofes, L.
Abstract : Background and purpose: The role of afferent sensory pathways in the pathophysiology of post‐stroke oropharyngeal dysphagia is not known. We hypothesized that patients with chronic post‐stroke dysphagia (PSD) would show impaired sensory cortical activation in the ipsilesional hemisphere. Methods: We studied 28 chronic unilateral post‐stroke patients [17 PSD and 11 post‐stroke non‐dysphagic patients (PSnD)] and 11 age‐matched healthy volunteers. Event‐related sensory‐evoked potentials to pharyngeal stimulation (pSEP) and sensory thresholds were assessed. We analyzed pSEP peak latency and amplitude (N1, P1, N2 and P2), and neurotopographic stroke characteristics from brain magnetic resonance imaging. Results: Healthy volunteers presented a highly symmetric bihemispheric cortical pattern of brain activation at centroparietal areas (N1–P1 and N2–P2) to pharyngeal stimuli. In contrast, an asymmetric pattern of reduced ipsilesional activation was found in PSD (N2–P2; P = 0.026) but not in PSnD. PSD presented impaired safety of swallow (penetration–aspiration score: 4.3 ± 1.6), delayed laryngeal vestibule closure (360.0 ± 70.0 ms) and higher National Institute of Health Stroke Scale (7.0 ± 6.2 vs. 1.9 ± 1.4, P = 0.001) and Fazekas scores (3.0 ± 1.4 vs. 2.0 ± 1.1; P < 0.05) than PSnD. pSEP showed a unilateral delay at stroke site exclusively for PSD (peak‐latency interhemispheric difference vs. PSnD: N1, 6.5 ± 6.7 vs. 1.1 ± 1.0 ms; N2, 32.0 ± 15.8 vs. 4.5 ± 4.9 ms; P < 0.05). Conclusions: Chronic post‐stroke oropharyngeal dysphagia is associated with stroke severity and degree of leukoaraoisis. Impaired conduction and cortical integration of pharyngeal sensory inputs at stroke site are key features of chronic PSD. These findings highlight the role of sensory pathways in the pathophysiology of post‐stroke oropharyngeal dysphagia and offer a potential target for future treatments.